Evaluation of the hygrothermal properties of thermal rendering systems - Joana Maia (2018)
The search for building envelopes with enhanced thermal properties is pursued to comply with European directives for lowering reference U-values. Thermal renders present low thermal conductivity, compared to traditional renders, and combine good thermal properties with easy application by mechanical spraying. The main goal of this work is to evaluate and compare the hygrothermal performance of three thermal render systems for different European climates. An extensive laboratory characterisation, measuring physical and hygrothermal material properties, was performed. It was verified that thermal conductivity linearly increases with water content, so thermal performance can be directly compromised if hygric behaviour is unfavourable. Porosity and microstructure were found to have a significant impact on other properties because the distribution of open and enclosed pores lead to different results. The high proportion of mesopores contributes to relevant moisture content during the lifetime of the building. The hygrothermal simulation demonstrated that the finishing coatings have a significant impact on the hygrothermal behaviour of the whole system. The application of thermally improved facades implies an increase in the temperature difference across different layers, especially in the thermal render, which could promote thermal stresses. As exterior insulation, the analysed systems showed that the simulated External Thermal Insulation Composite System (ETICS) exhibits good performance in general. However, the condensation potential is higher for ETICS, in particular, compared to thermal render systems. Consequently, an optimum compromise among thermal, hygric, and physical properties should be made.